2020
DOI: 10.21203/rs.3.rs-65351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed Region-Based Monitoring in Low-Power Listening Wireless Sensor Networks

Abstract: Advancement in IoT technology and the concept of Information-Centric Networking lead to less importance of node individuality since several nodes can work interchangeably. Multiple sensor nodes can be grouped into a region and monitored as one instance to guarantee sufficient coverage over the region. Therefore, a single node fault often does not need to be reported unless it is the last node in the region. In addition, there are occasions where a central monitor station cannot rely on continuous data deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It was implied that most of private clinics under UC can manage their own resources to provide healthcare service efficiently. The average pure technical efficiency score (TEVRS) was reach at 0.98, it was consistent with previous study of Pattamsiriwat that studied the efficacy and cost of the hospital office of the permanent secretary, Ministry of Public Health in the financial sector finance research program evaluating the impact of universal health care coverage on hospital finance (Pattamasiriwat, 2009), the result showed that average efficiency of center hospitals, general hospital and community hospitals were 0.94, 0.86, and 0.85, respectively. However, the result was different from the study in health sub-district offices in 2008, efficiency scores (DEA, VRS assumption) range from 0.60 to 0.75 and averaged to 0.69.…”
Section: Descriptive Statistics Of Technical and Scale Efficiency Scoressupporting
confidence: 89%
See 2 more Smart Citations
“…It was implied that most of private clinics under UC can manage their own resources to provide healthcare service efficiently. The average pure technical efficiency score (TEVRS) was reach at 0.98, it was consistent with previous study of Pattamsiriwat that studied the efficacy and cost of the hospital office of the permanent secretary, Ministry of Public Health in the financial sector finance research program evaluating the impact of universal health care coverage on hospital finance (Pattamasiriwat, 2009), the result showed that average efficiency of center hospitals, general hospital and community hospitals were 0.94, 0.86, and 0.85, respectively. However, the result was different from the study in health sub-district offices in 2008, efficiency scores (DEA, VRS assumption) range from 0.60 to 0.75 and averaged to 0.69.…”
Section: Descriptive Statistics Of Technical and Scale Efficiency Scoressupporting
confidence: 89%
“…Pattamsiriwat studied the efficacy and cost of the hospital office of the permanent secretary, Ministry of Public Health in the financial sector finance research program evaluating the impact of universal health care coverage on hospital finance (Pattamasiriwat, 2009). The study was based on the annual hospital financial report, the input variables were the number of patients, the number of outpatients and average relative weight while input variables were salaries and wages, compensation, service costs, number of beds, and number of personnel.…”
Section: Applications Of Dea In Healthcarementioning
confidence: 99%
See 1 more Smart Citation